Overcoming Pakistan's nuclear dangers - Fitzpatrick, Mark (Adelphi (Series) (International Institute for Strategic Studies), 2014)
Pakistan's nuclear arsenal - the fastest growing in the world - raises concerns on many grounds. Although far from the scale of the Cold War, South Asia is experiencing a strategic arms race. And the more weapons there are, the more potential for theft, sabotage and nuclear terrorism. Worries that Pakistan's nuclear-weapons technology might again be transferred to nuclear aspirants have not been expunged. Being outside the nuclear club makes it harder to ensure nuclear safety. Of gravest concern is the potential for a nuclear war, triggered by another large-scale terrorist attack in India with Pakistani state fingerprints as in the 2008 Mumbai atrocity, this time followed by an Indian Army reprisal. Lowering the nuclear threshold, Pakistan has vowed to deter this with newly introduced battlefield nuclear weapons. Mark Fitzpatrick evaluates each of the potential nuclear dangers, giving credit where credit is due. Understanding the risks of nuclear terrorism and nuclear accidents, Pakistani authorities have taken appropriate steps. Pakistan and India give less attention, however, to engaging each other on the issues that could spark a nuclear clash. The author argues that to reduce the nuclear dangers, Pakistan should be offered a formula for nuclear legitimacy, tied to its adopting policies associated with global nuclear norms.